Analisis Pengukuran Kualitas Website Sistem Informasi Universitas Bina Darma Menggunakan Metode Webqual 4.0 - Sagala, Nita Friskila; Sopiah, Nyimas; Marlindawati, Marlindawati (Teknik Informatika Universitas Pamulang, 2023)
Students in Bina Darma University's Information Systems class utilize a special website to research topics discussed in class, so that the quality of the site is relevant to their education. By using the webqual 4.0 method—focusing on usability, information quality, and service interaction quality—this research seeks to measure user (student) satisfaction. Partial acceptance of the hypotheses H1, H2, and H3 was achieved based on the t test results obtained with the values X1, This is shown by the t table test value of 1.995. Student satisfaction levels may be influenced by factors such as usability of the service, quality of information, and quality of user interaction with the service.